2009
DOI: 10.1002/app.30112
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of poly(butylene terephthalate) nanocomposites with various organoclays

Abstract: Layered-silicate-based polymer-clay nanocomposite materials were prepared depending on the surface modification of montmorillonite (MMT). Nanocomposites consisting of poly(butylene terephthalate) (PBT) as a matrix and dispersed inorganic clay modified with cetyl pyridinium chloride (CPC), benzyl dimethyl N-hexadecyl ammonium chloride, and hexadecyl trimethyl ammonium bromide by direct melt intercalation were studied. The organoclay loading was varied from 1 to 5 wt %. The organoclays were characterized with X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 14 publications
1
8
0
2
Order By: Relevance
“…High viscosity PBT nanocomposites show improved mechanical, dynamic mechanical properties [16]. Several experimental studies conducted on PBT clay nanocomposites can be found in the literature [6,[13][14][15][16][17][18][19][20][21][22][23]. In this paper, PCN containing Nylon6 is referred to as Nylon6-PCN and the PCN containing PBT is referred to as PBT-PCN.…”
Section: Introductionmentioning
confidence: 99%
“…High viscosity PBT nanocomposites show improved mechanical, dynamic mechanical properties [16]. Several experimental studies conducted on PBT clay nanocomposites can be found in the literature [6,[13][14][15][16][17][18][19][20][21][22][23]. In this paper, PCN containing Nylon6 is referred to as Nylon6-PCN and the PCN containing PBT is referred to as PBT-PCN.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction between the MMT and the VD or CTAB readily occurred for 6 h. Then the organo‐MMT containing double bonds (VMMT) was obtained after washing with water and diethyl ether several times, filtering, and drying in a vacuum oven. In order to compare with VMMT, the organo‐MMT (OMMT) modified with CTAB without double bonds was also prepared as reported in the literature …”
Section: Methodsmentioning
confidence: 99%
“…This result is similar to a study reported by Nirukhe and Shertukde on the effect of surface treatments and content of montmorillonite (MMT) on PBT. 25 They revealed that the addition of MMT significantly reduced the impact strength of the PBT/MMT composites, regardless the surface treatment of MMT, from approximately 52 MPa to 10 MPa for untreated MMT and to 20-30 MPa for treated MMT. It is also worth noting that the impact strength has similar trend to elongation at break where the addition of dolomite has detrimental effect on the composites.…”
Section: Impact Strengthmentioning
confidence: 97%